Electronic resource management in libraries [electronic resource] : research and practice - Breivold, Scott; Yu, Holly (Hershey, PA : Information Science Reference, 2008)
"This book provides comprehensive coverage of the issues, methods, theories, and challenges connected with the provision of electronic resources in libraries, with emphasis on strategic planning, operational guidelines, and practices. Its primary focus
"Premier reference source"--Cover
Description based on print version record
Includes bibliographical references (p. 383-408) and index
Keywords: Electronic information resources -- Management; Libraries -- Special collections -- Electronic information resources